ABOUT THE REPO AGREEMENT IN RUSSIAN LEGISLATION (Barqaror Taraqqiyot va Rivojlanish Tamoyillari, 2024)
The article deals with the repurchase agreement in the Russian legislation. The article analyzes the rules governing the grounds for concluding and terminating a repurchase agreement, the subject of the agreement, and defines the rights and obligations of the parties. In many respects, the norm contained in the law «On the securities market» does not sufficiently regulate relations under the repurchase agreement, so we have to refer to the Civil Code of the Russian Federation and other regulatory legal acts. The necessity of introducing a rule on the repurchase agreement by the legislator is justified. The author compares the concepts of «repurchase agreement» and « repurchase operations». The article reveals the weak legal regulation of the repo agreement in Russia and some other problems of this agreement.